Pengaruh pengetahuan ibu terhadap keberhasilan toilet training pada anak usia prasekolah: Systematic review - Ahmad Suryawan; Shella Permata Sari; Shalma Alya Fadilla; Woro Setia Ningtyas (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2023)
Background: In the Health Profile of the Republic of Indonesia, it is reported that the number of children under five (aged 1-5 years) is 23,960,310. From this amount, it is estimated that the number of children under five who have difficulty controlling bowel and bladder as well as bowel and bladder in any place until preschool age reaches 46% of the total number of children under five in Indonesia.Purpose: To identify the relationship or correlation between mother's knowledge and the success of toilet training in preschool children.Method: A systematic review was conducted based on the flow diagram of the Preferred Reporting Item for Systematic Review and Meta-Analysis (Prisma). The source of the article data was searched through four databases, Pubmed, Google Schoolar, Garuda Portal and Dimension to find appropriate keywords in Indonesian and English. Terms and keywords related to toilet training, toilet training success and mother's knowledge about toilet training. This study is based on a review of 928 clinical and research articles published between 2017-2022.Results: The finding of the ten articles used in this systematic review, eight of them showed a significant relationship between mothers' knowledge and the success of toilet training in preschoolers.Conclusion: Mother's knowledge is one of the most important factors for the success of toilet training in preschool children.Keywords: Mother; Knowledge; Toilet Training; Preschool; Children; Health.Pendahuluan: Dalam Profil Kesehatan Republik Indonesia, dilaporkan jumlah balita (usia 1-5 tahun) sebanyak 23.960.310 balita. Dari jumlah tersebut, diperkirakan jumlah balita yang susah mengontrol BAB dan BAK serta BAB dan BAK disembarang tempat sampai usia prasekolah mencapai 46% anak dari jumlah balita yang ada di Indonesia.Tujuan: Untuk mengidentifikasi hubungan atau korelasi antara pengetahuan ibu terhadap keberhasilan toilet training pada anak usia prasekolah.Metode: Penelitian systematic review yang dilakukan berdasarkan alur Prisma Guideline. Sumber data artikel dilakukan pencarian melalui empat data base yaitu Pubmed, Google Schoolar, Portal Garuda dan Dimension untuk mencari kata kunci yang sesuai dalam bahasa indonesia dan bahasa inggris. Istilah serta kata kunci yang berhubungan dengan toilet training, keberhasilan toilet training dan pengetahuan ibu tentang toilet training. Penelitian ini berdasarkan pengkajian dari 928 artikel klinis dan penelitian yang dipublikasikan antara 2017-2022.Hasil: Didapatkan sepuluh artikel yang dipakai dalam systematic review ini delapan diantaranya menunjukkan adanya hubungan yang signifikan antara pengetahuan ibu dengan keberhasilan toilet training pada anak usia prasekolah.Simpulan: Pengetahuan ibu merupakan salah satu faktor yang paling penting terhadap keberhasilan toilet training pada anak usia prasekolah.